Evaluasi Program Gerakan Sekolah Sehat Pada Smp Negeri 3 Arut Selatan Kabupaten Kotawaringin Barat: Evaluation of the Healthy School Movement Program at State Junior High School 3 Arut Selatan, West Kotawaringin Regency - Sugianto, Bambang; M. Fatchurahman; Kartini, Nurul Hikmah (Anterior Jurnal, 2026)
Health is a fundamental aspect that supports the success of education. The Indonesian government, through the Healthy School Movement (Gerakan Sekolah Sehat/GSS), seeks to create school environments that are clean, safe, friendly, and foster healthy living habits. This study aims to evaluate the implementation of the GSS program at SMP Negeri 3 Arut Selatan, Kotawaringin Barat Regency, using the CIPP (Context, Input, Process, Product) evaluation model to examine program relevance, resource readiness, implementation quality, and achieved outcomes. This research employed a qualitative approach with an evaluative method. Data were collected through observation, interviews, and documentation involving the principal, GSS team, teachers, and students. The data were analyzed through reduction, presentation, and conclusion drawing to identify key patterns and meanings emerging from the field. The findings revealed that the implementation of the GSS program was categorized as good across all evaluation components. The context aspect showed alignment between school needs and program goals. The input aspect indicated readiness in terms of human resources, infrastructure, and funding. The process aspect demonstrated that activities, schedules, and monitoring were carried out effectively. Meanwhile, the product aspect showed that students’ understanding and application of healthy behaviors reached 80%. The study concludes that the GSS program at SMP Negeri 3 Arut Selatan has been effectively implemented, though improvements are needed in consistent monitoring and the provision of supporting facilities. Recommendations include strengthening collaboration with local health offices, enhancing learning media for health education, and reinforcing continuous evaluation to ensure the sustainability and impact of the program.